Salt level for finishing swine - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two feeding trials involving 118 finishing Pigs were conducted to determine minimum salt needed in finishing diets. Performance of pigs fed 0.2 to 0.5% salt diets did not differ significantly, but pigs fed 0.1% or no salt gained significantly slower and less efficiently. Therefore, 0.2% salt in the finishing ration for swine from 100 lbs. to 215 lbs. should meet finishing pigs' requirements.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Salt; Finishing pigs; Performance